Sunflower HaGPAT9-1 is the predominant GPAT during seed development - Paya-Milans, Miriam; Antonio Aznar-Moreno, Jose; Balbuena, Tiago S. [UNESP]; Haslam, Richard P.; Gidda, Satinder K.; Perez-Hormaeche, Javier; Mullen, Robert T.; Thelen, Jay J.; Napier, Johnathan A.; Salas, Joaquin J.; Garces, Rafael; Martinez-Force, Enrique; et al. (Elsevier B.V., 2016)
In oil crops, triacylglycerol biosynthesis is an important metabolic pathway in which glycerol-3-phosphate acyltransferase (GPAT) performs the first acylation step. Mass spectrometry analysis of developing sunflower (Helianthus annuus) seed membrane fractions identified an abundant GPAT, HaGPAT9 isoform 1, with a N-terminal peptide that possessed two phosphorylated residues with possible regulatory function. HaGPAT9-1 belongs to a broad eukaryotic GPAT family, similar to mammalian GPAT3, and it represents one of the two sunflower GPAT9 isoforms, sharing 90% identity with HaGPAT9-2. Both sunflower genes are expressed during seed development and in vegetative tissues, with HaGPAT9-1 transcripts accumulating at relatively higher levels than those for HaGPAT9-2. Green fluorescent protein tagging of HaGPAT9-1 confirmed its subcellular accumulation in the endoplasmic reticulum. Despite their overall sequence similarities, the two sunflower isoforms displayed significant differences in their enzymatic activities. For instance, HaGPAT9-1 possesses in vivo GPAT activity that rescues the lethal phenotype of the cmy228 yeast strain, while in vitro assays revealed a preference of HaGPAT9-1 for palmitoyl-, oleoyl- and linoleoyl-CoAs of one order of magnitude, with the highest increase in yield for oleoyl- and linoleoyl-CoAs. By contrast, no enzymatic activity could be detected for HaGPAT9-2, even though its over-expression modified the TAG profile of yeast. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Endoplasmic reticulum; Glycerol-3-phosphate acyltransferase; Helianthus annuus; Mass spectrometry; Triacylglycerol; Yeast